Molecular identification of Entamoeba species in savanna woodland chimpanzees (Pan troglodytes schweinfurthii) - Jirků-Pomajbíková, Kateřina; Čepička, Ivan; Kalousová, Barbora; Jirků, Milan; Stewart, Fiona; Levecke, Bruno; Modrý, David; Piel, Alex K; Petrželková, Klára J (Parasitology, 2016)
To address the molecular diversity and occurrence of pathogenic species of the genus Entamoeba spp. in wild non-human primates (NHP) we conducted molecular-phylogenetic analyses on Entamoeba from wild chimpanzees living in the Issa Valley, Tanzania. We compared the sensitivity of molecular [using a genus-specific polymerase chain reaction (PCR)] and coproscopic detection (merthiolate-iodine-formaldehyde concentration) of Entamoeba spp. We identified Entamoeba spp. in 72 chimpanzee fecal samples (79%) subjected to species-specific PCRs for six Entamoeba species/groups (Entamoeba histolytica, Entamoeba nuttalli, Entamoeba dispar, Entamoeba moshkovskii, Entamoeba coli and Entamoeba polecki ST2). We recorded three Entamoeba species: E. coli (47%), E. dispar (16%), Entamoeba hartmanni (51%). Coproscopically, we could only distinguish the cysts of complex E. histolytica/dispar/moshkovskii/nuttalli and E. coli. Molecular prevalence of entamoebas was higher than the prevalence based on the coproscopic examination. Our molecular phylogenies showed that sequences of E. dispar and E. coli from Issa chimpanzees are closely related to sequences from humans and other NHP from GenBank. The results showed that wild chimpanzees harbour Entamoeba species similar to those occurring in humans; however, no pathogenic species were detected. Molecular-phylogenetic methods are critical to improve diagnostics of entamoebas in wild NHP and for determining an accurate prevalence of Entamoeba species.
Keywords: Animals; feces; Feces; great apes; Grassland; polymerázová řetězová reakce; Polymerase Chain Reaction; Tanzania; Tanzanie; savannah; pastviny; Phylogeny; entamébóza; DNA, Protozoan; protozoální DNA; molecular diversity; sekvenční homologie nukleových kyselin; Pan troglodytes; nemoci lidoopů; Sequence Homology, Nucleic Acid; Ape Diseases; zvířata; fylogeneze; Entamoebiasis; Entamoeba; chimpanzee